Circulation of Human Respiratory Syncytial Virus Strains among Hospitalized Children with Acute Lower Respiratory Infection in Malaysia. (January 2013) - Etemadi, Mohammad Reza; Sekawi, Zamberi; Othman, Norlijah; Lye, Munn-Sann; Moghaddam, Faezeh Yazdani
Human respiratory syncytial virus (RSV) is a major viral pathogen associated with acute lower respiratory tract infections (ALRTIs) among hospitalized children. In this study, the genetic diversity of the RSV strains was investigated among nasopharyngeal aspirates (NPA) taken from children less than 5 years of age hospitalized with ALRTIs in Hospital Serdang, Malaysia. A total of 165 NPA samples were tested for the presence of RSV and other respiratory viruses from June until December 2009. RSV was found positive in 83 (50%) of the samples using reverse transcription polymerase chain reaction (RT-PCR). Further classification of 67 RSV strains showed that subgroups A and B comprised 11/67 (16.4%) and 56/67 (83.6%) of the strains, respectively. The second hypervariable region at the carboxyl-terminal of the G gene was amplified and sequenced in order to do phylogenetic study. The phylogenetic relationships of the samples were determined separately for subgroups A and B using neighbor joining (NJ), maximum parsimony (MP), and Bayesian inference (BI). Phylogenetic analysis of the 32 sequenced samples showed that all 9 RSV-A strains were clustered within NA1 genotype while the remaining 23 strains of the RSV-B subgroup could be grouped into a clade consisted of strains with 60-nucleotide duplication region. They were further classified into newly discovered BA10 and BA9 genotypes. The present finding suggests the emergence of RSV genotypes of NA1 and BA. This is the first documentation of the phylogenetic relationship and genetic diversity of RSV strains among hospitalized children diagnosed with ALRTI in Serdang, Malaysia.